The COMFORT Trial: A Randomised Control Trial Comparing Group‐Based COMpassion‐FOcused Therapy Techniques and Breathing Pattern ReTraining With Treatment as Usual on the Psychological Functioning of Patients Diagnosed With Cancer Recurrence - Sinead Lynch; Rachel Pender; Carolyn Ingram; Clodagh Finnerty; Damien Lowry; Yvonne O'Meara; Donal J. Brennan (Cancer Medicine)
ABSTRACT Objective Although cancer‐related distress has been well researched, few studies explicitly address distress triggered by a recurrent diagnosis. We developed a patient‐informed, innovative, online intervention and performed a Randomised Control Trial (RCT) investigating the efficacy of combining Compassion‐Focused Therapy (CFT) techniques and Breathing Pattern Retraining (BPR) on the reduction of distress in patients with recurrence compared with Treatment as Usual (TAU). Our hypothesis was COMFORT would be more effective at reducing overall indices of distress than treatment as usual in patients with recurrent cancer. Methods One hundred sixty patients with recurrent disease and a Distress Thermometer (DT) score >/= 4 were enrolled and randomised to receive either 6 weeks of COMFORT or TAU. Data were collected via self‐report questionnaires at baseline (T1), post 6‐week intervention (T2) and at 12 weeks (T3). The primary outcome was change in DT score at 18 weeks. A linear mixed effects model was used to compare change from baseline between groups, accounting for repeated measures within individuals. A random intercepts model was used, with categorical time, group and time × arm interaction as fixed effects. Results One hundred sixty patients enrolled and 123 completed the protocol at 18 weeks. Participants mean age was 57 (SD‐14). Over 50% had breast or gynecological cancer. Patient demographics were well matched between groups. Linear mixed‐effects model and intent‐to‐treat analyses demonstrated a mean difference in the improvement in distress from baseline to 18 weeks of 1.09 units (95% CI: 0.24, 1.95) (p = 0.013) on the DT in the intervention group, consistent with the pre‐specified minimum clinically significant difference. Secondary endpoints demonstrated a significant reduction in patient‐reported distress in response to cancer as a traumatic event, and not significant but clinically important improvements in anxiety, depression and adjustment to cancer. Conclusions COMFORT demonstrates that an online intervention met its primary outcome of distress reduction. Further multisite trials are required.